Prevalence and clinical significance of left bundle branch block according to classical or strict definition criteria in permanent pacemaker patients - Mazza, Andrea (Clin Cardiol, 2017)
BACKGROUND: Previous studies have shown that the presence of left bundle branch block (LBBB) is associated with an increased risk of cardiac mortality and heart failure (HF). Recently, new criteria to define strict LBBB have been proposed: QRS duration ≥140 ms for men and ≥130 ms for women, along with mid‐QRS notching or slurring in ≥2 contiguous leads. HYPOTHESIS: We assessed the prevalence and prognostic significance of LBBB according to classical (QRS duration ≥120ms) and strict criteria in permanent pacemaker patients. METHODS: We retrospectively enrolled 723 consecutive patients who had undergone single‐ or dual‐chamber pacemaker implantation at the study center from July 2002 to December 2014. Patients with a left ventricular ejection fraction ≤35% or a prior diagnosis of HF were excluded. RESULTS: LBBB was reported in 54 (7%) patients, and strict‐LBBB in 15 (2%) patients. During a median follow‐up of 48 months (range, 18–92 months), 147 (20%) patients reached the combined endpoint of death or HF hospitalization. Patients with LBBB and those with strict‐LBBB displayed significantly higher rates of death or HF hospitalization (log‐rank test, all P < 0.0001). In particular, strict‐LBBB was associated with the worst outcome. The presence of LBBB according to classical definition criteria (hazard ratio [HR] = 1.98, confidence interval [CI]: 1.23‐3.19, P = 0.005) and to strict criteria (HR = 2.20; CI: 1.04‐4.65; P = 0.039) were both confirmed as independent predictors of death or HF hospitalization after adjustment for relevant clinical covariates. CONCLUSIONS: Among patients who had undergone standard pacemaker implantation, the prevalence of LBBB was 7% according to classical definition criteria and 2% according to strict criteria. The presence of LBBB, and particularly of strict‐LBBB, at the baseline predicted a poor outcome in terms of death or HF hospitalization.